IoT with BlockChain: A Futuristic Approach in Agriculture and Food Supply Chain. (23rd June 2021) - Awan, Sabir; Ahmed, Sheeraz; Ullah, Fasee; Nawaz, Asif; Khan, Atif; Uddin, M. Irfan; Alharbi, Abdullah; Alosaimi, Wael; Alyami, Hashem
Abstract : Agricultural food production is projected to be 70% higher by 2050 than it is today, with the world population rising to more than 9 billion, 34% higher than it is now. The farmers have been forced to produce more with the same resources. This pressure means that optimizing productivity is one of the main objectives of the producers but also in a sustainable way. Not only does agriculture face a decline in production, but it has also had to face limitations in data collection, storing, securing, and sharing, climate change, increases in input prices, traditional food supply chain systems where there is no direct connection between the farmer and the buyer, and limitations on energy use. Existing IoT-based agriculture systems have a centralized format and operate in isolation, leaving room for unresolved issues and major concerns, including data security, manipulation, and single failure points. This paper proposes a futuristic IoT with a blockchain model to meet these challenges. Further, this paper also proposes and novel energy-efficient clustering IoT-based agriculture protocol for lower energy consumption and network stability and compares its results with its counterpart low-energy adoptive clustering hierarchy (LEACH) protocol. The simulation results show that the proposed protocol network stability is 23% higher as compared to LEACH as first node of LEACH dies at 168 rounds while IoT-based agriculture first node dies after 463 rounds. Similarly, IoT-based agriculture protocol energy consumption is 68% lower than that of LEACH. The proposed protocol also extends the network life to more rounds and demonstrates an increase of 112%.